RESEARCH OF THE OPERATIONAL CHARACTERISTICS OF BITUMEN, WHICH MODIFIED WITH POLYETHYLENE WASTE - Satayeva, S.S.; Imangaliyeva, A. I. (Science and education №1, 2019)
In this work the BND 70/100 oil asphalt from the Aktau Bitumen Factory LLP «CaspiBitum» was considered. An asphalt was modified with polymer waste to upgrade operating properties. The И-40industrial oil was used as a softener. Indicators like penetration, ductility, brittleness temperature and softening temperature of bitumen were explored in this study. It was shown, that physical-mechanical properties of bitumen increased after modification: needle penetration depth decreased, extensibility decreased, softening temperature increased. Also, the influence of polymers on the structure of bitumen and the effect of their action in the composition were examined. Structure of polymer waste in Republic of Kazakhstan was analyzed. It was proved, that the usage of the recycled polyethylene as a modifier is a rational approach, and it lets to recycle stocks of secondary polymeric materials. Also problems of improving the properties of polymer-bitumen binder and ecology solved.В работе исследован нефтяной дорожный битум марки БНД 70/100 Актауского битумного завода ТОО «Caspi Bitum». Для улучшения эксплуатационных свойств проведено модифицирование дорожного битума полимерными отходами. В качестве пластификатора использовано индустриальное масло марки И-40. Изучены следующие показатели дорожного битума: пенетрация, растяжимость (дуктильность), температура хрупкости, температура размягчения. Показано, что после модифицирования физико-механические свойства битума улучшаются: сокращается глубина проникновения иглы, уменьшается растяжимость, повышается температура размягчения. Также изучено влияние полимеров на структуру битумов, эффект их действия в композиции. Проанализированы полимерные отходы в Республике Казахстан. Доказано, что применение в качестве модификатора вторичного полиэтилена является рациональным подходом, позволяющим переработать запасы вторичного полимерного сырья, при этом решаются проблемы улучшения свойства полимер-битумного вяжущего и экологии.
Keywords: научный журнал; периодическое издание; отечественное издание; битум; нефтяной продукт; дорожный битум; asphalt, polymer waste; brittleness temperature; penetration; modification